THE IMPACT OF COSMETOLOGICAL PROCEDURES ON STRIAE AFFECTED WOMEN SKIN - Auškalnė, Raimonda; Stungienė, Lina (PROFESSIONAL STUDIES: Theory And Practice, 2024)
The article analyses the effect of cosmetic procedures on women's skin affected by striae, the impact of stretch marks on women's quality of life and presents the research data describing respondents' knowledge about stretch marks, their correction possibilities, and their impact on quality of life. The research data is compared with the findings of studies conducted by foreign authors.